2003
DOI: 10.1007/s00592-003-0091-1
|View full text |Cite
|
Sign up to set email alerts
|

Body composition analysis for healthy Italian vegetarians

Abstract: The elementary nutritional needs of vegetarians are totally, or in great part, supplied by vegetarian food; thus the body composition of vegetarians could differ from that of omnivorous persons. The objective of the present study was to compare healthy Italian vegetarians to healthy omnivorous individuals in terms of body composition, determined using dual X-ray absorptiometry. The study population consisted of 20 vegetarians [mean age (+/-SD), 34.78+/-15.07 years; mean BMI, 22.41+/-2.15 kg/m(2)] and 10 omnivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 6 publications
1
10
1
Order By: Relevance
“…Most of the studies conducted with vegetarians do not mention BMI lowest values, but in one study [22] conducted with vegetarian and no vegetarian women about 17% of all participants had BMI lower than 20, and the distribution was similar in both groups. Usually [23][24][25] vegetarian men's BMI is higher or similar to women's, but this was not found in this research in accordance to only one previous study [26].…”
Section: Discussioncontrasting
confidence: 78%
“…Most of the studies conducted with vegetarians do not mention BMI lowest values, but in one study [22] conducted with vegetarian and no vegetarian women about 17% of all participants had BMI lower than 20, and the distribution was similar in both groups. Usually [23][24][25] vegetarian men's BMI is higher or similar to women's, but this was not found in this research in accordance to only one previous study [26].…”
Section: Discussioncontrasting
confidence: 78%
“…Furthermore, although vegans in this study had a very low intake of dietary calcium (375 g/day) compared to omnivores (683 g/day), there was no correlation between calcium intakes and BMD. We also found no difference in either lean mass or fat mass between vegetarians and omnivores, and this finding is consistent with a recent study on 20 vegans and ten omnivorous individuals of Caucasian background [23]. Thus, our and others' data suggest that veganism does not induce any adverse change in body composition.…”
Section: Age (+5years)supporting
confidence: 81%
“…Despite these consistently-observed differences in BMI between vegetarians and non-vegetarians, obesity is common among some populations that follow largely vegetarian diets, such as Indians living in the UK 15 and in India 16 . Regarding body composition, in one comparative study on anthropometric and metabolic indexes among Italian male and female, no significant differences between groups were found in terms of hand grip and back strength, suggesting that there was no association between vegetarian diet and body composition 17 . However, in the present study, we found that the grip strength was statistically significantly higher among the non-vegetarian groups as compared to the vegetarian groups.…”
Section: Discussionmentioning
confidence: 97%